The Effectiveness of Using Mobile Learning Application on Undergraduates’ Intrinsic Motivation and Their General Nutrition Knowledge - AlKasasbeh, Walaa Jumah; Amawi, Adam Tawfiq (International Journal of Interactive Mobile Technologies (iJIM), 2023)
This research aims to investigate the effectiveness of using a mobile learning application on undergraduates’ intrinsic motivation and their general nutrition knowledge. This quasi-experimental study involved the participation of 125 students who were divided into two groups: a control group consisting of 62 students and an experimental group comprising 63 students. Pre- and post-intrinsic motivation questionnaires and a nutritional knowledge test were administered. The results showed significant differences between the control group and the experimental group. The experimental group exhibited a higher level of knowledge, and there were no statistically significant differences in intrinsic motivation between the control group and the experimental group. The application was found to be effective in improving nutrition knowledge but did not enhance intrinsic motivation. Further research may be needed to understand the factors that influence intrinsic motivation and how to effectively increase it.